Foreign policy matters: a normative view of the G8 and population health - Ronald Labonte; Ted Schrecker (The World Health Organization, 2007)
The Group of Eight (G8) countries occupy a dominant position in the international economic and political order. Given what is known about influences on the social determinants of health in an interconnected world, the G8 are a logical starting point for any enquiry into the relations between foreign policy and health. We first make five arguments for adopting an explicitly normative, equity-oriented perspective on the performance of G8 policy in areas related to population health. We then examine G8 performance with respect to the crucial policy triad of development assistance, debt relief and trade, finding that neither rhetoric nor promising institutional innovation has been matched by resources commensurate with demonstrated levels of need. We conclude that it is necessary to pursue advocacy efforts based on the normative perspective we have put forward and that doing so effectively requires further investigation of why some polities are more receptive than others to policies of redistribution both within and outside their borders.